1994
DOI: 10.1111/j.1365-2141.1994.tb08305.x
|View full text |Cite
|
Sign up to set email alerts
|

P‐glycoprotein expression on acute myeloid leukaemia blast cells at diagnosis predicts response to chemotherapy and survival

Abstract: P-glycoprotein (Pgp) expression, which is associated with the multi-drug resistance (MDR) phenotype, has been reported to be a useful predictor of treatment outcome in acute leukaemia. We have examined the expression of Pgp on acute myeloid leukaemia (AML) cells in 54 newly diagnosed patients, using a novel streptavidin-biotin complex (ABC) technique. 55% of patients at diagnosis were positive for Pgp with JSB-1, a monoclonal antibody that binds to an internal epitope of Pgp. All patients received intensive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
2
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(52 citation statements)
references
References 25 publications
3
45
2
1
Order By: Relevance
“…The role of PGP in the determination of clinical multidrug resistance in leukaemia is more uncertain (Haber, 1992). However, this problem is of particular interest as (1) the MDR caused by PGP involves several first-line drugs used in leukaemic chemotherapy, such as vinca alkaloids, anthracyclines and epipodophyllotoxins (Tsuruo, 1988); (2) in cell lines showing mdr-1 gene amplification, a wide range of drugs can block PGP function and restore drug sensitivity (Ford et al, 1990); (3) in leukaemia, many authors have already reported that PGP over-expression is frequent and can predict lower remission rates and a higher frequency of relapse (Campos et al, 1992a;Michieli et al, 1992;Ino et al, 1994;Wood et al, 1994;Zöchbauer et al, 1994).…”
mentioning
confidence: 99%
“…The role of PGP in the determination of clinical multidrug resistance in leukaemia is more uncertain (Haber, 1992). However, this problem is of particular interest as (1) the MDR caused by PGP involves several first-line drugs used in leukaemic chemotherapy, such as vinca alkaloids, anthracyclines and epipodophyllotoxins (Tsuruo, 1988); (2) in cell lines showing mdr-1 gene amplification, a wide range of drugs can block PGP function and restore drug sensitivity (Ford et al, 1990); (3) in leukaemia, many authors have already reported that PGP over-expression is frequent and can predict lower remission rates and a higher frequency of relapse (Campos et al, 1992a;Michieli et al, 1992;Ino et al, 1994;Wood et al, 1994;Zöchbauer et al, 1994).…”
mentioning
confidence: 99%
“…25,26 However, several authors have already reported that Pgp overexpression is associated with lower remission rates and poor prognosis. 6 A simple and sensitive method to detect Pgp in tumor cells is provided by immunohistochemical staining with monoclonal antibody. 6 Nuclear chromatin pattern has been reported to be changed in drug-selected human MDR cells and not in other MDR cells without drug selection.…”
Section: Discussionmentioning
confidence: 99%
“…6 A simple and sensitive method to detect Pgp in tumor cells is provided by immunohistochemical staining with monoclonal antibody. 6 Nuclear chromatin pattern has been reported to be changed in drug-selected human MDR cells and not in other MDR cells without drug selection. 27 However, the ALLm patients in this study were not exposed to any chemotherapeutic drugs before and no ALLm cases showed Pgp expression before induction chemotherapy by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Although immunohistochemistry is a morphological means with inherent limitations concerning quantitative evaluation, many semiquantitative immunohistochemical studies provided evidence for the prognostic value of P-gp for patients' survival or a disease-free interval and corroboration has come from investigations measuring mRNA expression. [7][8][9][10] This speaks of some validity of immunohistochemistry in general. Nevertheless, the considerable inter-and intralaboratory variations presented at the American and French workshops hamper a reliable clinical routine application.…”
mentioning
confidence: 98%